Hallmarks of exercised heart. (March 2022) - Qiu, Yan; Pan, Xue; Chen, Yiwen; Xiao, Junjie
Abstract: The benefits of exercise in humans on the heart have been well recognized for many years. Long-term endurance exercise training can induce physiologic cardiac hypertrophy with normal or enhanced heart function, and provide protective benefits in preventing heart failure. The heart-specific responses that occur during exercise are complex and highly variable. This review mainly focuses on the current understanding of the structural and functional cardiac adaptations to exercise as well as molecular pathways and signaling proteins responsible for these changes. Here, we summarize eight tentative hallmarks that represent common denominators of the exercised heart. These hallmarks are: cardiomyocyte growth, cardiomyocyte fate reprogramming, angiogenesis and lymphangiogenesis, mitochondrial remodeling, epigenetic alteration, enhanced endothelial function, quiescent cardiac fibroblast, and improved cardiac metabolism. A major challenge is to explore the underlying molecular mechanisms for cardio-protective effects of exercise, and to identify therapeutic targets for heart diseases.